Inheritance Law in Minangkabau: A Comparative Study of the Application of Islamic and Customary Inheritance Law in Koto Tangah Subdistrict and Nanggalo Padang City: (Hukum Waris di Minangkabau: Studi Komparatif Penerapan Hukum Waris Islam dan Adat di Kec. Koto Tangah dan Nanggalo Kota Padang) - Rahmadanil, Rahmadanil; Zuwanda, Rifka (El-Qist: Journal of Islamic Economics and Business (JIEB), 2021)
Abstract: Inheritance, according to Minangkabau custom, is given to girls, not boys. In Islam, property inheritance is regulated by Far?i? fiqh, which gives to daughters, sons, spouses of heirs (husband or wife) and even the inheritor's parents. Property inherited from generation to generation in the Minangkabau community is called "pusaka tinggi” which means high heritage. In contrast, the legacy of the parents' livelihood is called "pusaka rendah” which means low inheritance. This article wants to answer about how the inheritance of the Minangkabau community in Koto Tangah Subdistrict and Nanggalo Padang City Subdistrict. The authors use a qualitative research model and an empirical juridical approach, with the data in this article obtained from interviews, observations and document studies. The result is that the distribution of the Minangkabau community's inheritance in Koto Tangah Subdistrict and Nanggalo Padang City Subdistrict is divided into two. "Pusaka tinggi" which is the people's property and cannot be traded, will always be inherited, controlled and owned from generation to generation from the traditional female line. While the "pusaka rendah" is individual property, the inheritance distribution follows the Heir religion; if Moslem, then Far?i? fiqh can be applied. Keywords: Inheritance Law; High Heirloom; Low Inheritance; Minangkabau custom.   Abstrak: Harta peninggalan menurut adat masyarakat Minangkabau diberikan kepada anak perempuan bukan kepada anak laki-laki. Sedangkan dalam Islam, peninggalan harta diatur oleh ilmu Far?i? yang memberikan kepada anak perempuan, anak laki-laki, pasangan pewaris (suami atau istri) bahkan orang tua pewaris. Harta hasil warisan turun temurun di masyarakat Minangkabau disebut “pusaka tinggi” sedangkan peninggalan hasil pencaharian orang tua disebut “pusaka rendah”. Artikel ini ingin menjawab tentang bagaimana pembagian harta waris masyarakat Minangkabau di Kecamatan Koto Tangah dan Nanggalo Kota Padang. Penulis menggunakan model penelitian kualitatif dan pendekatan yuridis empiris, dengan data dalam artikel ini diperoleh dari hasil wawancara, observasi dan studi dokumen. Hasilnya, bahwa pembagian harta waris masyarakat Minangkabau di Kecamatan Koto Tangah dan Nanggalo Kota Padang dibedakan menjadi dua. “Pusaka tinggi’ yang merupakan harta Kaum dan tidak dapat diperjualbelikan akan selalu diwarisikan, dikuasai dan dimiliki secara turun temurun dari garis perempuan secara Adat. Sedangkan “pusaka rendah” yang notabennya harta individual, pembagian warisnya mengikuti agama Pewaris, jika Muslim maka ilmu Far?i? dapat diterapkan. Kata Kunci: Hukum Waris; Pusaka Tinggi; Pusaka Rendah; Adat Minangkabau.